2000
DOI: 10.1097/00043764-200009000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Effects of Exposure to Stainless Steel and Mild Steel Welding Fumes

Abstract: Over the past few years, many studies, including one on our previous work, have examined the chronic effects of fumes from stainless steel (SS) welding on the health of welders. These chronic effects have been related to concentrations of chromium and nickel in SS welding fumes. The present study examined the acute respiratory effects of welding fumes in the workplace by measuring the across-shift changes in a population of 144 SS and mild steel (MS) welders and 223 controls. Manual Metal Arc, Metal Inert Gas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
2
30
0
1
Order By: Relevance
“…According to the measurements obtained during simulated challenge tests, welding fumes of mild steel principally produced iron and manganese, whereas stainless steel produced a lesser amount of these, but a higher amount of chromium (table 1). These results are well in line with previous literature [11]. The composition of Duplex fumes was similar to that of stainless steel, but the former had somewhat higher proportions of chromium in the inhalable dust and also traces of molybdenum.…”
Section: Discussionsupporting
confidence: 92%
“…According to the measurements obtained during simulated challenge tests, welding fumes of mild steel principally produced iron and manganese, whereas stainless steel produced a lesser amount of these, but a higher amount of chromium (table 1). These results are well in line with previous literature [11]. The composition of Duplex fumes was similar to that of stainless steel, but the former had somewhat higher proportions of chromium in the inhalable dust and also traces of molybdenum.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, this effect was related more to welding on stainless steel as compared to mild steel, and to manual metal arc welding as compared to MIG welding. 5 Some studies have suggested that welding-related exposures may cause asthma. 6,7 Most studies are limited by a lack of information on the types, durations, and intensities of workers' exposures.…”
Section: Discussionmentioning
confidence: 99%
“…JNAP employees posted notices at several locations in the plant to let co-workers know that a team from NIOSH would visit the plant from February [8][9][10]2006 and that physicians on the team would be available to meet with them privately at the UAW Local 7 Union Hall located across the street from the plant. In addition to these face-to-face interviews, we also obtained information from employees who contacted us via telephone.…”
Section: Additional Informationmentioning
confidence: 99%
“…In a recent study, this effect was related more to welding on stainless steel as compared to mild steel, and to manual metal arc welding as compared to MIG welding. 8 Some studies have suggested that welding-related exposures may cause asthma. 9,10 Most studies are limited by a lack of information on the types, durations, and intensities of workers' exposures.…”
Section: Respiratory Disease In Weldersmentioning
confidence: 99%